An exploration of midwives’ approaches to slow progress of labour in birth centres, using case study methodology - Iannuzzi, Laura (2016)
Background: Slow progress of labour (SPL) occurs in 3-37% of all labours. It constitutes the main cause of primary caesarean section (CS) and is associated with operative births, maternal and foetal morbidity, and a negative birthing experience. SPL is also the principal reason for the transfers of women from midwife-led units (MLUs) or their home, to hospitals. The current standard medical management of SPL, including intravenous administration of synthetic oxytocin and artificial rupture of membranes (ARM), has been increasingly questioned and the need for alternatives recommended. A midwifery approach to SPL represents a possible important alternative. However, contemporary literature shows a surprising dearth of research concerning midwives’ approaches to SPL. Birth centres appear ideal settings for exploring a midwifery approach to SPL, given the strong midwifery philosophy and the relevance of SPL reported in these contexts.